Engineering Alfalfa to Produce 2-O-Caffeoyl-L-Malate (Phaselic Acid) for Preventing Post-harvest Protein Loss via Oxidation by Polyphenol Oxidase - Sullivan, Michael L.; Green, Heather A.; Verdonk, Julian C. (Frontiers in Plant Science, 2021)
Many plants accumulate high levels of hydroxycinnamoyl esters and amides in their tissues, presumably to protect against biotic and abiotic stress. Red clover (Trifolium pretense) leaves accumulate high levels (5-15 mmol/kg fresh weight [FW]) of caffeic acid derivatives, including phaselic acid (2-O-caffeoyl-L-malate). Oxidation of caffeoyl-malate by an endogenous polyphenol oxidase (PPO) has been shown to help preserve forage protein after harvest and during storage as silage, which should improve N use efficiency in dairy and other ruminant production systems. The widely grown forage alfalfa lacks both PPO and PPO substrates and experiences substantial loss of protein following harvest. We previously identified a hydroxycinnamoyl-coenzyme A (CoA):malate hydroxycinnamoyl transferase (HMT, previously called HCT2) responsible for phaselic accumulation in red clover. With the goal of producing PPO-oxidizable compounds in alfalfa to help preserve forage protein, we expressed red clover HMT in alfalfa. Leaves of these alfalfa accumulated mainly p-coumaroyl- and feruloyl-malate (up to 1.26 and 0.25 mmol/kg FW, respectively). Leaves of HMT-expressing alfalfa supertransformed with an RNA interference (RNAi) construct to silence endogenous caffeoyl-CoA acid O-methyltransferase (CCOMT) accumulated high levels of caffeoyl-malate, as well as the p-coumaroyl and feruloyl esters (up to 2.16, 2.08, and 3.13 mmol/kg FW, respectively). Even higher levels of caffeoyl- and p-coumaroyl-malate were seen in stems (up to 8.37 and 3.15 mmol/kg FW, respectively). This level of caffeoyl-malate accumulation was sufficient to inhibit proteolysis in a PPO-dependent manner in in vitro experiments, indicating that the PPO system of post-harvest protein protection can be successfully adapted to alfalfa.